Training and Mentoring: Preparation of Digitization-Based Quality Indicators at Bunda General Hospital: Pelatihan dan Pendampingan: Penyusunan "Indikator Mutu" Berbasis Digitalisasi di Rumah Sakit Umum Bunda - Pipit Festi Wiliyanarti; Neneng Dewi; Donny Permana; Linda Hapsari; Heru Suswojo; Anisa Nurida; Sholihul Absor; Yuanita Wulandari; Mundakir (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
A reliable internal quality assurance system is one of the keys to ensuring the hospital management process is in accordance with the vision and mission as well as improving quality and patient safety. The purpose of this community service was to conduct training and mentoring at Bunda General Hospital to develop digitization-based priority quality indicators. The community service methods that have been applied include mentoring and training to 40-unit leaders. The media used were leaflets, logbooks, and training manuals. This community service was carried out in December 2023. At the end of the activity, the results showed an increase in the knowledge of the head of the unit in compiling hospital quality indicators. The increase in knowledge and skills in preparing quality indicators before training has an average score of 45, after training knowledge and skills increase with an average score of 91. Training and assistance to unit heads at Bunda Hospital in compiling quality indicators is needed as a benchmark for unit performance to improve the quality of Bunda Hospital services. The quality of hospital services can be improved directly with intensive assistance in compiling performance indicators.